A Serious Game for Mediated Education on Traffic Behavior and Safety Awareness - Apostolia Gounaridou; Eleni Siamtanidou; Charalampos Dimoulas (MDPI AG, 2021)
Computer games are considered a useful tool for educational purposes. Alternative media applications such as serious games combine edification with challenge and entertainment. Thus, learning becomes enjoyable, more comfortable, and more efficient. The paper presents the implementation of an educational computer game regarding traffic behavior awareness through the main stages of analysis, design, development, and evaluation, aiming at investigating the contribution of gamification in traffic safety. The game was developed as an advanced media education approach in Unreal Engine, encompassing various adventures. The game hero's tasks are to move into the virtual city to complete a mission, follow road safety rules, and experience the adventures either as a pedestrian or as a vehicle driver. Research hypotheses/questions are tested concerning the gaming impact and the audience engagement through first-person storytelling to communicate and perceive traffic regulations. The results reveal that a properly developed educational game could become more engaging, amusing, and efficient. It could also enhance traffic awareness through experiential and mediated learning, also fostering social responsibility.